1-(4-Carboxyphenyl)-5-methyl-1H-1, 2, 3-triazole-4-carboxylic acid – A versatile ligand for the preparation of coordination polymers and mononuclear complexes. (15th May 2021) - Bratanovici, Bogdan-Ionel; Shova, Sergiu; Lozan, Vasile; Dascălu, Ioan-Andrei; Ardeleanu, Rodinel; Roman, Gheorghe
Graphical abstract: Examination of the potential of the title ligand for the generation of coordination compounds with transition metal ions led to the isolation of novel Cd(II)-based networks and Cu(II)-based complexes. Cd(II)-containing networks derived from this ligand that also incorporate co-ligands (4, 4′-bipyridine or 4, 4′-azopyridine) in their structure have been described for the first time. Abstract: The straightforward and facile synthetic approaches towards four coordination polymers, {[CdL(H2 O)]·0.5H2 O}n, {[Cd2 L2 (H2 O)2 (4, 4′-bipy)]·4H2 O}n, {[Cd2 L2 (H2 O)2 (4, 4′-azpy)]·3H2 O}n and {[CoL(H2 O)3 ]·2.5H2 O}n (4, 4′-bipy = 4, 4′-bipyridine; 4, 4′-azpy = 4, 4′-azopyridine), based on the polydentate ligand 1-(4-carboxyphenyl)-5-methyl-1 H -1, 2, 3-triazole-4-carboxylic acid (LH2 ) and Cd(II) and Co(II) ions are reported. In addition, two mononuclear complexes, [Cu(HL)2 (DMA)] and [Cu(HL)2 (H2 O)2 ], derived from the same ligand and the Cu(II) ion have been prepared. The coordination compounds have been characterized by infrared spectroscopy, thermogravimetry, powder X-ray diffraction and elemental analysis. Single crystal X-ray structures for each of these coordination compounds have been established. The specific surface of the 3D Cd(II)- and Co(II)-derived coordination polymers, determined through nitrogen adsorption, is negligible (SBET  < 25 m 2 /g).